An empirical analysis of the impact of institutions on economic growth: Evidence from Latin American countries - Topolewski, Łukasz (Publishing House of Wroclaw University of Economics and Business, 2025)
Aim: The aim of this article was to assess the impact of institutions on economic performance, using Latin American countries in the period of 1996-2021 as a case study. Methodology: Data for this study were obtained from the World Bank and United Nations Development Programme. In this study, the measures proposed by Kaufmann and Kraay were employed. The study’s time frame spanned the period 1996 to 2021. The geographical scope included 21 Latin American economies. Dynamic panel models were employed. Results: The results revealed that institutions play a fundamental role in driving economic growth. The establishment of a proper set of institutions is essential for a country to escape from the poverty trap. Despite Latin American countries sharing similarities in terms of language, religion, and historical colonisation by European countries, they demonstrate significant economic disparities. For instance, Chile and Uruguay were able to successfully implement reform measures that set them on a path of economic growth. Implications and recommendations: To achieve a high rate of economic growth, it is crucial to establish a suitable institutional framework. This leads to the conclusion that institutions serve as the primary driver of economic growth. Originality/value: The problem of the impact of institutions on economic growth is discussed in the literature and has been the subject of empirical research. In this article, the empirical verification was carried out on the basis of Latin American countries, which is the originality of this study. In this way, it was confirmed on a new dataset that institutions do matter. On the other hand, it should be noted that Latin American countries, considered similar, are not so similar.
Argumenta Oeconomica, 2025, Nr 1 (54), s. 126-136
Keywords: institutions; economic growth; dynamic panel models; Latin American